2020
DOI: 10.1111/efp.12618
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds (VOC) as biomarkers for detection of Ceratocystis platani

Abstract: Ceratocystis platani causes canker stain of plane trees, and it represents a serious disease of Platanus spp. both in the United States and Europe. Current chemical or biological controls do not effectively manage C. platani, so new preventive methods need to be developed in order to limit this pathogen spreading. In this work, we have characterized the main volatile organic compounds (VOC) emitted in vitro from pure cultures of C. platani and other common pathogenic fungal species of hosts plants growing in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…This task is also complicated by the fact that some of the VOCs found in our study, e.g. isobutyl acetate, are also known fungal volatiles 76 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This task is also complicated by the fact that some of the VOCs found in our study, e.g. isobutyl acetate, are also known fungal volatiles 76 …”
Section: Discussionmentioning
confidence: 97%
“…isobutyl acetate, are also known fungal volatiles. 76 Numerous plant-insect-microorganism interactions have been investigated so far 77 which clearly show high variability in synergistic and antagonistic impacts on plant performance. A recent meta-analysis highlighted important information on the insect herbivore preference and performance on fungus-challenged plants.…”
Section: Discussionmentioning
confidence: 99%
“…No VOCs detected were uniquely, and consistently, emitted from F. circinatum-inoculated seedlings. Therefore, no single VOC detected here can independently be used as a reliable indicator of disease, which also rules out the idea of identifying a F. circinatum-specific VOC emitted regardless of growth medium, as could be done 31 . This means that multivariate data analysis, preferably using a machine learning-based pipeline as presented in this study, is required.…”
Section: Tablementioning
confidence: 90%
“…However, Vuorinen et al 28 could distinguish birch trees exposed to pathogens or herbivores on the basis of VOC profiles, and similarly Johne et al 29 could differentiate between two pathogenic fungi in horse chestnut trees (Aesculus spp.). It has been shown that VOCs may serve as an indicator of fungal infection in asymptomatic spruce 30 and recently, Brilli et al 31 found a few VOCs to be uniquely emitted from Ceratocystis platani-infected asymptomatic Platanus trees, highlighting the potential for targeted VOCs analysis for disease detection. Further method development is needed for VOCs applications in the forestry field.…”
mentioning
confidence: 99%
“…Therefore, using compounds that differ quantitatively to differentiate between healthy and diseased plants may lead to erroneous classifications when environmental conditions and other biotic stressors are variable and sampling methods are inconsistent. Brilli et al [53] successfully used a targeted approach, where plane trees infected with Ceratocystis platani were readily distinguishable from healthy controls using a few compounds that were uniquely present in the infected trees. We similarly saw disease-exclusive compounds, but unlike Brilli et al [53], our unique compounds were likely not from the pathogens themselves.…”
Section: Discussionmentioning
confidence: 99%